KAJIAN STRUKTUR BETON BERTULANG 10 LANTAI PADA PEMBANGUNAN GEDUNG SEKRETARIAT KONI PROVINSI KALIMANTAN TIMUR - WATY, TRISNA (KURVA S JURNAL MAHASISWA, 2016)
Building construction is one of the most frequently used. For that the additional floor in the Secretariat Building construction KONI East Kalimantan Province is because space in the building is inadequate, it is planned to be 10 floors previously planned 8 floors.In planning the building in the analysis using the two methods used in Matrix and SAP 2000 which aims to determine the loads acting on a portal and to determine the moment that occurs due to loading. For foundation piles were used that were adapted to the ground data.From the results of the analysis results obtained load acting on a portal that is dead loads, live loads and wind loads. Based on the results of comparative analysis of the structure with the two methods taken the greatest moment so that the value obtained, the beam Mu = 41.835 tons/ m, column Pu = 158.873 tons / m, sloof Mu = 14.251 ton / m. Based on the calculation of the foundation found the number of different pole each position located then at the end position amounted to 3 pole and 2 pole positions amounted middle.